Description of Paraxiopsis kensleyi n. sp., a new axiid lobster from the Gulf of Mexico (Crustacea: Decapoda: Axiidea) - Felder, Darryl L. (Zootaxa, 2021)
A new species of axiid was discovered during sampling offshore deep banks on the middle continental shelf off Louisiana. Paraxiopsis kensleyi n. sp. appears to inhabit interstices and cavities of coralline algal rubble, rhodoliths, coral rubble, and other eroded calcareous substrates. Weakly separated from Eutrichocheles Wood-Mason, 1876 on the basis of morphology, present assignments of western Atlantic species to Paraxiopsis de Man, 1905 are regarded as provisional. The new species is described morphologically, and the coloration of freshly captured specimens is documented and compared to related species where possible. Coloration readily distinguishes mature specimens of the new species from Paraxiopsis spinipleura Kensley, 1996, with which it was initially confused. The diagnosis includes GenBank accession numbers for COI sequences to allow future molecular phylogenetic comparisons. Compared to regional species that share a similar dentation or spination on the submedian carina, the pleon of the new species is distinctive in the truncate ventral margin on pleura 2–4, as opposed to being broadly rounded or directed ventrally in an acutely triangular tip. The new species is the eighteenth species of Paraxiopsis worldwide and the ninth from western Atlantic waters, seven of which are now known to range into the Gulf of Mexico. An updated key to western Atlantic members of the genus is provided.